Технологія гібридної модифікації гуміновими кислотами бурого вугілля плівок гідроксипропілметилцелюлози - Лебедєв, Володимир Володимирович; Мірошниченко, Денис Вікторович; Савченко, Дмитро Олександрович; Черкашина, Ганна Миколаївна; Литвиненко, Євгенія Ігорівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
Розглянуто особливості технології гібридної модифікації гуміновими кислотами бурого вугілля біодеградабельних плівок на основі гідроксипропілметилцелюлози. В результаті проведених досліджень вперше отримано гібридні біодеградабельні плівки з антибактеріальними властивостями. При одержані біодеградабельних плівок використовували використовували гідроксипропілметилцелюлозу марки Walocel, в якості каталізатора зшивання біодеградабельних полімерних плівок використовується лимонна кислота (99,88 %) за ГОСТ 3652. У рамках досліджень методом ІЧ-спектроскопії фактично визначено гібридні структури гідроксипропілметилцелюлози, модифікованої різними типами гуміновими кислотами. У результаті дослідження встановлено закономірності зміни часу появи плісняви плівок в рамках технології гібридної модифікації гуміновими кислотами бурого вугілля. Також встановлено, що технологія гібридної модифікації гуміновими кислотами бурого вугілля плівок гідроксипропілметилцелюлози із наданням їм антибактеріальних властивостей дозволяє зберегти властивості біодеградації. Встановлено, що технологія гібридної модифікації гідроксіпропілметилцелюлози гуміновими кислотами бурого вугілля біодеградабельних плівок гідроксіпропілметилцелюлози різними типами гумінових кислот при наданні їм антибактеріальних властивостей дозволяє мати біодеградацію плівкам на їх основі не менше 91% впродовж 6 місяців при оптимальному вмісті гумінових кислот 10 % мас. Отримані згідно технології гібридної модифікації гуміновими кислотами бурого вугілля біодеградабельна плівки з бактерицидними властивостями на основі гідроксипропілметилцелюлози за своїми експлуатаційними характеристиками перевершують відомі аналогічні біодеградабельна плівки на основі природних біополімерів та можуть бути рекомендовані для виготовлення пакування сухих харчових продуктів (хліб, крупи, горіхи тощо) з подовженим терміном зберігання.

The peculiarities of the technology of hybrid modification of lignite humic acids of biodegradable films based on hydroxypropylmethylcellulose are considered. As a result of the conducted research, hybrid biodegradable films with antibacterial properties were obtained for the first time. Hydroxypropylmethylcellulose of the Walocel brand was used for the production of biodegradable films, and citric acid (99.88%) according to GOST 3652 is used as a catalyst for crosslinking biodegradable polymer films. As part of the research, the hybrid structures of hydroxypropylmethylcellulose modified with different types of humic acids were actually determined by IR spectroscopy. As a result of the study, the regularities of changes in the time of appearance of mold of films within the framework of the technology of hybrid modification with lignite humic acids were established. It was also established that the technology of hybrid modification of hydroxypropylmethylcellulose films with humic acids of lignite and giving them antibacterial properties allows to preserve the properties of biodegradation. It was established that the technology of hybrid modification of hydroxypropylmethylcellulose with lignite humic acids of biodegradable hydroxypropylmethylcellulose films with different types of humic acids, while giving them antibacterial properties, allows the biodegradation of films based on them to be at least 91% within 6 months with an optimal humic acid content of 10% by mass. Biodegradable films with bactericidal properties based on hydroxypropylmethylcellulose, obtained according to the technology of hybrid modification with humic acids of lignite, in terms of their operational characteristics, are superior to known similar biodegradable films based on natural biopolymers and can be recommended for the manufacture of packaging of dry food products (bread, cereals, nuts, etc.) with an extended storage period.
Technology of hybrid modification with humic acids of brown coal hydroxypropylmethyl cellulose films
Keywords: гібридна модифікація; гумінові кислоти; буре вугілля; біодеградабельні плівки гідроксипропілметилцелюлози; hybrid modification; humic acids; brown coal; biodegradable films of hydroxypropyl methylcellulose